A self-operated polymer electrolyte fuel cell system operating at dead-end conditions using pure hydrogen and oxygen gases - Yang, Cheolnam; Moon, Sungmo; Kim, Yangdo (Journal of mechanical science and technology, 2015)
The present study reports the system configurations of a self-operated Polymer electrolyte fuel cell (PEFC) that is specially designed for dead-end operation of both pure hydrogen and oxygen gas lines, including its operation features and durability. The PEFC stack with 16 unit cells was constructed using homemade membrane electrode assemblies with 300 cm 2 of apparent active area and bipolar plates. A self-operated PEFC system was developed using a homemade PEFC stack, balance of plant, and electric control unit for automatic fuel cell system operation. Performance parameters of the self-operated PEFC system, including fuel utilization, parasitic loss, released heat, purge loss, and efficiency of the PEMFC stack and system were evaluated during the automatic operation of the PEFC system. A Daily start-and-stop (DSS) test was also performed for one month to check the durability of the self-operated PEFC system. Electric efficiencies of the PEFC stack and system are approximately 60% and 49%, respectively, at an operating condition of 1.1 kW electric output; no performance degradation of the PEFC system was observed for a month during the DSS test.